2013
DOI: 10.5114/pg.2013.39918
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics of patients with diagnosed functional dyspepsia

Abstract: IntroductionThe term “dyspepsia” comes from the Greek words “dys’ and ‘peptin”, which maen “ill digestion” or indigestion, although this set of symptoms in the adult clinic has little to do with the digestion or absorption process, and refers more to ailments related to the upper section of the gastrointestinal tract.AimAssessment of the frequency of functional dyspepsia diagnosis, the characteristics of the group and an attempt to identify the accompanying symptoms, assessment of histological lesions and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
11
1
3
Order By: Relevance
“…The majority of Google users live in the northern hemisphere; thus, seasonal variations in the time series mainly reflected this population. The peaks of interest in pain-related topics reflected previously reported relationships of pain location and the season for Headaches [51], viral infection of the upper airways (Ear pain, Sore throat), heartburn [52] or angina pectoris (Chest pain) [53], Abdominal pain [54,55], Low back pain [56], sexual activity (Dyspareunia) [57], and injuries (limb pain) [58]. Interestingly, the lowest RSVs for most of the topics were observed in December, which may be associated with the seasonal holidays, when people's attention could be away from the Internet.…”
Section: Time Coursementioning
confidence: 61%
“…The majority of Google users live in the northern hemisphere; thus, seasonal variations in the time series mainly reflected this population. The peaks of interest in pain-related topics reflected previously reported relationships of pain location and the season for Headaches [51], viral infection of the upper airways (Ear pain, Sore throat), heartburn [52] or angina pectoris (Chest pain) [53], Abdominal pain [54,55], Low back pain [56], sexual activity (Dyspareunia) [57], and injuries (limb pain) [58]. Interestingly, the lowest RSVs for most of the topics were observed in December, which may be associated with the seasonal holidays, when people's attention could be away from the Internet.…”
Section: Time Coursementioning
confidence: 61%
“…B, There was also no significant difference in lag time (P = 0.64) is lower than the average age of FD patients. 32 Previous studies showed that the largest group of FD patients is aged between 46 and 60 33 and that the prevalence of dyspeptic symptoms increases with age. 34 However, whether age affects the variables assessed in the current study is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Function dyspepsia (FD) is highly prevalent all over the world [ 1 , 2 ]. A previous study found that middle-aged and elderly people were prone to suffer from FD [ 3 ]. Although FD rarely affects patient mortality [ 4 ], it can have a bad impact on the quality of patients’ lives [ 5 ].…”
Section: Introductionmentioning
confidence: 99%